A lab-on-injector device with Au nanodots confined in carbon nanofibers for in situ electrochemical BPA sensing in beverages. (April 2022) - Lei, Yanan; Zhang, Yuhuan; Wang, Beibei; Zhang, Zhong; Yuan, Li; Li, Jianke
Abstract: Bisphenol A (BPA) as the most common endocrine disruptor used in food containers and packaging is causing adverse effects for human beings. Accordingly, in situ detection of BPA is of practical importance for food safety. However, the complicated operations of existed methods and interference of various impurities in food matrix restrict the realization of real-time in situ BPA sensing in food samples. We report here a portable and fully-integrated electrochemical sensing device with an injector as the reaction vessel which assembled with screen printed electrodes (SPEs) as sensing electrodes and a detachable filter unit to filter impurities. This device, namely lab-on-injector, reduces the sampling, pretreatment and detection to a simple on-step operation, making in situ detection of BPA in real samples much easier and more feasible. Moreover, extra-small Au nanodots confined in carbon nanofibers (AuNDs@CNFs) were synthesized by in situ carbothermic reduction of Au 3+ absorbed on cellulose, and were used to modified SPEs surface to greatly enhance detection performance of the lab-on-injector. Using this AuNDs@CNFs based lab-on-injector, BPA in food matrix was detected directly with recoveries from 93.14% to 94.25%, demonstrating a reliable platform for in situ detection of BPA, and opening a new way for the development of smart devices in electroanalysis. The electrochemical behaviors of BPA oxidation on AuNDs@CNFs/GCE were further explored. CVs of AuNDs@CNFs/GCE with different scan rates were recorded (Fig. S4). Whether the electrochemical reaction of BPA is a diffusion-controlled or surface-controlled process can be determined by the following equations. Highlights: A novel electrochemical lab-on-injector device was assembled for in situ detection of BPA. AuNDs@CNFs nanocomposite were prepared to greatly enhance the sensing performance for BPA. The developed device displayed high sensitivity, excellent selectivity and reproducibility in BPA detection. The device was successfully applied for the in situ determination of BPA in different beverages.